Complications of the Bacillus Calmette-Guerin vaccine as an early warning sign of inborn errors of immunity: a report of 197 patients - Fazlollahi, Mohammad Reza; Goudarzi, Ali; Nourizadeh, Maryam; Alizadeh, Zahra; Tajik, Shaghayegh; Badalzadeh, Mohsen; Sarafzadeh, Shokouh Azam; Mahlooji Rad, Maryam; Adab, Zeinab; Moradi, Leila; Razaghian, Anahita; Sabetkish, Nastaran; et al. (Frontiers in Immunology, 2024)
BackgroundAccording to the WHO’s recommendation for developing countries, Bacillus Calmette-Guerin (BCG) vaccination has been implemented in some countries as part of national vaccination programs at birth. Although it is generally considered safe, some complications may occur; including BCGitis (local) or BCGosis (systemic), ranging from mild like local abscesses to fatal impediments like osteomyelitis and disseminated BCG infection. This study aimed to determine the spectrum of inborn errors of immunity (IEI) in BCG-vaccinated neonates experiencing local or systemic complications.MethodsIn this cross-sectional study, we investigated Iranian children referred to the Immunology, Asthma, and Allergy Research Institute (IAARI) between 2007-2023 for suspected immunodeficiency. Medical history was recorded, and primary screening tests for immunodeficiency were conducted for all cases. For suspected cases, more advanced immunologic investigations were performed to reach a definitive diagnosis. Furthermore, the study incorporated the documented genetic findings of the patients under investigation. All patients with inborn error of immunity who had a history of BCG vaccine complications within the first year of vaccination were enrolled in the study.ResultsWe investigated 3,275 cases suspected of IEI, identifying197 patients with both IEI and BCG vaccine complications. Among these, 127 (64.5%) were male. Symptoms began at or before 3 months of age in 64.8% of the cases, and parental consanguinity was reported in 79.2%. Genetic diagnoses were confirmed in 108 patients. Of the 197 patients, 108 (54.8%) had BCGitis, while 89 (45.2%) experienced systemic complications (BCGosis). A family history of IEI, BCG-related complications, and unexplained deaths were observed in 20.3%, 12.2%, and 29.9% of cases, respectively. Furthermore, 46.2% had at least one of these three risk factors in their history.ConclusionsEarly BCG vaccine complications may indicate an underlying immunodeficiency, particularly when there is a positive family history of BCG complications, immunodeficiency, or unexplained deaths. Nation-wide vaccination protocols should address this issue by delaying inoculation to allow for immunological screening of suspected immunodeficient patients, thereby preventing BCG vaccine-related morbidity and mortality.